2007
DOI: 10.1007/s11596-007-0217-8
|View full text |Cite
|
Sign up to set email alerts
|

The roles of four multi-drug resistance proteins in hepatocellular carcinoma multidrug resistance

Abstract: The roles of multi-drug resistance protein 1 (MDR1), multi-drug resistance related protein 1 (MRP1), lung resistance protein (LRP) and breast cancer resistance protein (BCRP) in the multi-drug resistance (MDR) of hepatocellular carcinoma (HCC) were studied. By exposing HepG2 cell line to progressively increased concentrations of adriamycin (ADM), HepG2 multi-drug resistant subline (HepG2/ADM) was induced. The MDR index of HepG2/ADM was detected by using MTT. The expressions of the four MDR proteins in the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 8 publications
2
34
0
1
Order By: Relevance
“…It has been suggested that overexpression of P-gp but not MRP1 mainly contributes to the MDR of SMMC-7721/ADM cells (Yan et al, 2010). The upregulation of P-gp and BCRP but not MRP1 and LRP are involved in the MDR of HepG2/ADM cells (Li et al, 2007;Sun et al, 2010). Overexpression of P-gp is also a predominant mechanism to explain the MDR in a taxol-resistant cell line, QGY-TR50 (Zhou et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that overexpression of P-gp but not MRP1 mainly contributes to the MDR of SMMC-7721/ADM cells (Yan et al, 2010). The upregulation of P-gp and BCRP but not MRP1 and LRP are involved in the MDR of HepG2/ADM cells (Li et al, 2007;Sun et al, 2010). Overexpression of P-gp is also a predominant mechanism to explain the MDR in a taxol-resistant cell line, QGY-TR50 (Zhou et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…As a potential explanation for this increased chemotherapy resistance, significantly increased expression levels of MDR1 (ABCB1) and MRP1 (ABCC1) were found; these genes are known to contribute to multidrug resistance in HCC (12)(13)(14)(15)17,18,20). MRP1, which is overexpressed in HCC (39), performs an important role in the intrinsic multidrug resistance of HCC and is also associated with an aggressive tumor phenotype and has been suggested to indicate a progenitor cell origin (18).…”
Section: Discussionmentioning
confidence: 99%
“…While a large proportion of doxorubicin is eliminated from the body unchanged, the main pathway of doxorubicin metabolism is two-electron reduction by cytosolic reductases, of which carbonyl reductase 1 is the most important in the liver (10). However, doxorubicin resistance in HCC cells is predominantly associated with the expression of adenosine triphosphate-binding cassette (ABC) transporters such as ABCB1 (multi-drug resistance gene; MDR1) or ABCC1 (multidrug resistance-associated protein 1; MRP1) (10,(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…After 48 hours' incubation, the cell viability was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, as described in an earlier publication. 31 Following this, the cell survival curves were drawn, from which the half maximal inhibitory concentration of the three agents was calculated.…”
Section: Drug-resistance Characteristics In Post-treated Cancer Cellsmentioning
confidence: 99%
“…The subsequent reverse transcription real-time polymerase chain reaction analyses were performed according to the procedure outlined in a previous study. 31 The primers were synthesized by Biocolors (Shanghai, People's Republic of China), with the oligonucleotide sequences as shown in Table 1.…”
Section: The Detection Of Microvessel Density In Post-treated Tumor Tmentioning
confidence: 99%